2018
DOI: 10.1097/md.0000000000010941
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective study of Ganoderma Lucidum Spore Powder for patients with epilepsy

Abstract: This study firstly investigated the feasibility effect and safety of Ganoderma Lucidum Spore Powder (GLSP) for treating patients with epilepsy.Eighteen eligible patients with epilepsy were included. They all received GLSP treatment for a total of 8 weeks. The primary outcome included weekly seizure frequency. The secondary outcomes consisted of each seizure episode, and quality of life, measured by the Quality of Life in Epilepsy Inventory-31 (QOLIE-31), as well as the adverse events (AEs).After treatment, GLS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…A retrospective study in 2018 included 18 patients with epilepsy who were treated with G. lucidum spore powder therapy three times per day for 8 weeks. The study revealed that the powder reduced the weekly seizure frequency and the severity of each seizure episode (Wang et al, 2018). Further studies are required to confirm its efficacy in treating human epilepsy.…”
Section: Ganoderma Lucidummentioning
confidence: 91%
See 1 more Smart Citation
“…A retrospective study in 2018 included 18 patients with epilepsy who were treated with G. lucidum spore powder therapy three times per day for 8 weeks. The study revealed that the powder reduced the weekly seizure frequency and the severity of each seizure episode (Wang et al, 2018). Further studies are required to confirm its efficacy in treating human epilepsy.…”
Section: Ganoderma Lucidummentioning
confidence: 91%
“…The herb powder could reduce average weekly seizure frequency from 3.1 ± 0.8 to 2.4 ± 1.2, but it didn't show significant differences of duration of epilepsy and quality of life. The most common adverse effect is nausea, the second one is stomach discomfort, then the others are vomiting, dizziness, dry mouth, diarrhea, sore throat, and epistaxis in order (Wang et al, 2018).…”
Section: Evidence-based Human Applicationsmentioning
confidence: 99%
“…Administration of hot water extracts from various herbs, including G. lucidum has been tested to relieve herpes zoster pain within a few days, and no patients developed post-herpetic neuralgia after more than one year of follow-up [344]. In 2018, a clinical study reported that weekly seizure frequency was reduced in patients with epilepsy after administration of G. lucidum spore powder [345]. In addition, G. lucidum also shows curative effects on depression in combination therapy [346].…”
Section: Neuroprotective Effects Of G Lucidummentioning
confidence: 99%
“…Certain mushrooms have not only nutritional value but also contain bioactive compounds with high medicinal properties. One such mushroom, the Ganoderma lucidum , is used across Asia as a nutraceutical and herbal remedy for many different ailments ( Ding et al, 2010 ; Batra et al, 2013 ; Collado Mateo et al, 2015 ; Wang et al, 2018a ; Geng et al, 2019 ). Ganoderma lucidum extract (GLE) has shown therapeutic benefits as an anti-diabetic agent, in breast cancer, and in inflammatory diseases such as colitis ( Martinez-Montemayor et al, 2011 ; Suarez-Arroyo et al, 2013 ; Liu et al, 2015 ; Barbieri et al, 2017 ; Geng et al, 2019 ; Liu and Tie, 2019 ; Yin et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%